(3eMGSHI GdJcGdjas (3GdGZQGV GdbjGS aj HjHFI GdJUfjY GdeYGUQIs - (3fhQ(B, (3CMeO eMeOs; (3TMGJgs ((3GdGScfOQjIs (3GdOGQ GdLGeYjIs, 2004)
(3gPG GdcJGH bSe Edi bSejf (B: (3GdbSe GdGhd bSe Cdi HGHjf , GdGhd eONd deMGSHI GdJcGdja (B: (3OhQI GdGOGQI hOhQI GdeMGSHI hGdfXGe GdeMGSHj , eLGd eMGSHI GdJcGdja hCgOGagG , GJLGgGJ GdJUfjY GdMOjKI hJCKjQgG Ydi eMGSHI GdJcGdja GdHGH GdKGfj GdeUWdMGJ GdQFjSjI ddJcGdja (B: (3eUWdMGJ GdJcGdja hGdGbSGe GdQFjSjI dgG , eSdc GdJcGdja OGdI GdJcdaI hOhQ GdeMGSHI GdJcGdja aj YedjI GdJNWjW , GdJcGdja aj eLGd GJNGP GdbQGQGJ, GdJcGdja aj eLGd GdQbGHI heHGOF eMGSHI GdeSDhdjI GdbSe GdKGfj bSe gh HOhQg Edi HGH hGMO haUhdg cGGdJGdj (B: (3fXGe GdJcGdja , OhQI JSLjd HjGfGJ GdJcGdja (B- (3GdfeGPL IGdbjhO GdeMGSHjI , GdSLdGJ GdeSJNOeI aj fXGe eMGSHI GdJcGdja , bjGS JcGdja CfTWI GdNOeGJ ,CSFdI hJWHjbGJ GdbSe GdKGfjs
Keywords: (3GdeMGSHI GdJMdjdjIs; (3eMGSHI GdJcGdjas